Al-TarbÄ«yah al-Mutaâ€™addidah al-ThaqÄfÄtÄ«yah: TanmÄ«yah al-Dimukraá¹Ä«yah bi IndÅ«nÄ«sÄ«yÄ - Namsa, M. Yunus (Studia Islamika, 2005)
This article presents a comprehensive study of the conflicts in Indonesia, using the conflict in North Maluku as a case study. As is well-known, the long-drawn-out conflict that began in 1999 resulted in many deaths. The Indonesian Government reported (based on 1999-2000 data) that about 1,842 people had died as a direct result of the conflict. Of that total, the majority (1,797) were civilians, while the policemen (32) and the army soldiers (13) accounted for a small amount of the death toll. Other sources reported that the actual death toll was in fact 2,084 people, with a further 1,003 seriously wounded and 756 with minor injuries. In addition to the loss of human life, and great deal of public and private property was also lost. This included 20,241 homes, 200 schools, and 144 places for worship (both mosques and churches).DOI:Â 10.15408/sdi.v12i3.584